Truth and commitment in theology and science: An appraisal of Wolfhart Pannenberg"s perspective - Van Huyssteen, J. Wentzel (Hervormde teologiese studies, 1989)
The Leitmotiv of Wolfhart Pannenberg’s work has always been his conviction that the Christian faith, and especially theology as a reflection on this faith, has a universal credibility in our age. This essay approaches this issue and sets forth a thesis in terms of the rationality of theology and of science. The shaping of rationality in both theology and science eventually forms the framework for dealing with the philosophical problems of truth, objectivity and commitment in Pannenberg’s impressive and ever expanding body of thought.